Increasing income of small and marginal farm families through integrated farming system in CDR Eco-System - Singh, S.K.; Singh2, Brij Vikash; Kumari, Kumari; Singh, I.P.; Kumar, Anant (Annals of Agricultural Research, 2018)
This study was undertaken in Auraiya district of Uttar Pradesh in central plan of agro-climatic zone where more than 53% of total geographical area covered under dense forests and hilly tracts. five villages were randomly selected from all the three community development blocks of the district with a sample size of 150 small and marginal farmers, 30 from each village. It was found that out of the eight farming systems followed by the resource poor farming community of Auraiya district, Rice-Wheat with a pair of bullock is the most prevalent farming system adopted by 34.0% of total farm households followed by Rice-Wheat-livestock. Rice-Pulse-horticulture crop combination was adopted by only 3.3% of total respondents. An on-farm-trial (OFT) to assess suitable integrated farming system( IFS) in one ha of land for the resource poor farmers of this complex, diversified and risk prone (CDR) central plain zone comprising of both crop (rice-green gram-early tomatoearly cauliflower) and non-crop components (poultry-mushroom-vermi compost) was tested by Krishi Vigyan Kendra, Auraiya during 2013-14. It was found that the gap of net income between the farming systems was Rs. 140993 rupees. BC ratio calculated was 2.82 and 1.75 of the recommended and traditional farming systems respectively. This recommended IFS was found valid for the resource poor farm families in central plain zone with increasing land use efficiency, sustaining livelihood by strengthening the economic status and generating employment using the land and time judiciously.